Measuring geographic proximity and continuity with family medicine at end-of-life: Protocol for a population-level retrospective cohort study using Canadian Health Administrative Data - Shuaib Hafid; Lawrence Mbuagbaw; Bruce Newbold; Andrew Costa; Ana Gayowsky; Peter Gozdyra; Aaron Jones; Sarina Isenberg; Erin Gallagher; Michelle Howard (PLoS ONE, 2025)
Background Family physicians play an important role in coordinating care for medically complex patients, especially during the end-of-life (EOL) period. While continuity of care (COC) is a routinely measured care quality indicator, the influence of geographic proximity to family physicians on EOL COC has not been studied in the Canadian context. Existing research has focused on rurality indicators instead of individual-level proximity measures. Objectives This study objectives are to: (1) measure the association between patients’ geographic proximity to their family physician and COC during the patients’ last year of life; and (2) measure the association between geographic proximity and the number of days spent in the community and palliative homecare services referral in the last year of life, and place of death. Methods We will conduct a population-level retrospective cohort study using linked health administrative data from ICES in Ontario, Canada, of adults who died between January 1, 2021, and December 31, 2024. Geographic proximity to the rostered family physician will be calculated in the shortest travel distance and time from the patient’s residence to the physicians primary practice location, considering road, transit, and walking infrastructure. COC will be measured using three indices: Usual Provider of Care, Modified Bice-Boxerman, and Relative Variance indices, based on outpatient visits in the last year of life. EOL outcomes will include days spent in the community, referral to palliative home care, and place of death. Multivariate regression will measure associations between proximity and outcomes, adjusting for relevant patient-level characteristics. Expected outcomes We hypothesize that patients living closer to their family physician will experience higher COC and improved healthcare outcomes at the end of life. Findings have the potential to inform health policy and planning aimed at improving equitable geographic access to family medicine during the late stages of life.